PENGAJARAN JIHAD DALAM KITAB FATH AL-BARI - Muhammad Amin (FORUM PAEDAGOGIK, 2019)
Jihad is one of the Islamic studies. In Fath Al-Bari book explained that jihad is to exert all abilities to fight the infidels. In other side, Jihad is also used in fighting the lust, evil and wicked person. Jihad in fighting the lust is through learning religion, practice and teaching it. Then, Jihad in fighting Satan or evil is by rejecting all (doubtful and lust) of his whisper. Meanwhile, jihad in fighting the evil is can be done by using property, verbal, and heart. The last Jihad in fighting the wicked person is by using verbal and heart.